Primary tubercular psoas abscess: a rare presentation - Kiran Chawla; Annet D’Souza; Shyamasunder Bhat N; Chiranjay Mukhopadhayay (Journal of Infection in Developing Countries)
Primary tubercular psoas abscess is a rare clinical entity and has seldom been reported in an otherwise healthy person. Here we report an interesting case of primary tubercular psoas abscess in an immunocompetent male with no other traceable source.